Percutaneous mechanical thrombectomy in patients with high-risk pulmonary embolism and contraindications for thrombolytic therapy - Bunc, Matjaž (Radiology and oncology (Ljubljana), 2020)
Background. High-risk pulmonary embolism is associated with a high early mortality rate. We report our experience with percutaneous mechanical thrombectomy in patients with high-risk pulmonary embolism and contraindications for thrombolytic therapy.Patients and methods. This was a retrospective analysis of consecutive patients with high-risk pulmonary embolism and contraindications to thrombolytic therapy. They were treated with percutaneous mechanical thrombectomy which included thrombectomy and additional thrombus aspiration when needed. Clinical parameters and survival to discharge were measured. Results. From November 2005 to September 2015 we treated 25 patients with a mean age of 62.6 +- 12.7 years, 64% were men. Mean simplified Pulmonary Embolism Severity Index was 2.9. Mean maximum lactate levels were 7.8 +- 6.6 mmol/L, vasopressors were used in 77%, and 59% needed mechanical ventilation. Mechanical treatment included thrombus fragmentation complemented with aspiration (56%) and aspiration using Aspirex S catheter (44%). Local (5 patients; 20%) and systemic (3 patients; 12%) thrombolytics were used as a salvage therapy. We observed nonsignifi-cant improvements in systemic blood pressure (100 +- 41 mm Hg vs 119 +- 34; p = 0.100) and heart frequency (99 +- 35 min-1vs 87 +- 31 min-1; p = 0.326) before and after treatment, respectively. Peak systolic tricuspid pressure gradient was significantly lower after treatment (57 +- 14 mm Hg vs 31 +- 3 mm Hg; p = 0.018). Overall the procedure was technically successful in 20 patients (80%) and 17 patients (68%) survived to hospital discharge. Conclusions. In patients with high-risk pulmonary embolism who cannot receive thrombolytic therapy, percutaneous mechanical thrombectomy is a promising alternative to reduce pulmonary artery pressure.
Keywords: perkutana mehanska trombektomija; pljučna embolija; zdravljenje